ASSESSMENT OF QUALITY OF LIFE IN WOMEN WITH UNDIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA - Kadimova, Sh.Q. (World of Medicine and Biology, 2024)
To study the quality of women’s life, based on developed clinical and laboratory criteria, for the period from 2019 to 2022, a prospective study of the course of pregnancy and its outcomes was conducted in 68 pregnant women aged 18 to 39 years (average age 27.98±5.3) with undifferentiated connective tissue dysplasia, which formed a high-risk group for the development of pathology of the fetoplacental system. The conducted studies found that the “physical component” and the “psychological component” of the quality of life in pregnant women are reduced equally, limiting household and social functioning. Possible ways to improve the quality of life of pregnant women were identified, affecting the reduced controllable characteristics of the state of health by means and methods of health improving physical culture.
Keywords: quality of life; postpartum period; placental insufficiency; pregnancy